The Making and Breaking of Serine-ADP-Ribosylation in the DNA Damage Response - Schützenhofer, Kira; Rack, Johannes Gregor Matthias; Ahel, Ivan (Frontiers in Cell and Developmental Biology, 2021)
ADP-ribosylation is a widespread posttranslational modification that is of particular therapeutic relevance due to its involvement in DNA repair. In response to DNA damage, PARP1 and 2 are the main enzymes that catalyse ADP-ribosylation at damage sites. Recently, serine was identified as the primary amino acid acceptor of the ADP-ribosyl moiety following DNA damage and appears to act as seed for chain elongation in this context. Serine-ADP-ribosylation strictly depends on HPF1, an auxiliary factor of PARP1/2, which facilitates this modification by completing the PARP1/2 active site. The signal is terminated by initial poly(ADP-ribose) chain degradation, primarily carried out by PARG, while another enzyme, (ADP-ribosyl)hydrolase 3 (ARH3), specifically cleaves the terminal seryl-ADP-ribosyl bond, thus completing the chain degradation initiated by PARG. This review summarises recent findings in the field of serine-ADP-ribosylation, its mechanisms, possible functions and potential for therapeutic targeting through HPF1 and ARH3 inhibition.